The effect of Lactobacillus brevis KB290 against irritable bowel syndrome: a placebo-controlled double-blind crossover trial - Murakami Katsumi; Habukawa Chizu; Nobuta Yukihiro; Moriguchi Naohiko; Takemura Tsukasa (BioPsychoSocial Medicine, 2012)
Abstract Background Irritable bowel syndrome (IBS) is a functional disorder of the digestive tract that causes chronic abdominal symptoms. We evaluated the effects of Lactobacillus brevis KB290 (KB290), which has been demonstrated to be effective at improving bowel movements and the composition of intestinal microflora, on IBS symptoms. Methods We performed a placebo control double-blind cross matched trial. Thirty-five males and females (aged 6 years and above) who had been diagnosed with IBS according to the Rome III criteria were divided into 2 groups, and after a 4-week pre-trial observation period, they were administered test capsules containing KB290 or placebo for 4 weeks (consumption period I). Then, the capsule administration was suspended for 4 weeks in both groups (washout period), before the opposite capsules were administered for a further 4 weeks (consumption period II). Fecal samples were collected on the first day of the pre-consumption observation period, the last day of consumption period I, the last day of the washout period, and the last day of consumption period II. In addition, the subjects’ IBS symptoms and quality of life (QOL) and any adverse events that they experienced were evaluated. Results No significant difference in IBS symptoms was noted among the various periods. However, the mean QOL scores were improved during the test capsule consumption. The frequencies of watery and mushy feces were significantly lower in the test capsule consumption period than during the pre-consumption observation period, and the frequency of abdominal pain was significantly reduced in the test capsule consumption period compared with the other periods. The frequency of the genus Bifidobacterium was significantly higher, and that of the genus Clostridium was significantly lower, after the test capsule consumption than after the placebo consumption. The frequencies of the genera Lactobacillus, Bacteroides, and Enterococcus were also investigated, but no differences in their frequencies were detected between the placebo and test capsule consumption periods. Conclusions Probiotics, the safety of which has been established, are used widely in various foods and can now be purchased readily. The results of the present study suggest that KB290 is useful for early intervention in IBS.